Processos criativos no desenvolvimento da musicalidade de professoras unidocentes - Ferreira, Heloise Gomes (2019)
This research described and analysed creative processes in the development of the musicality of primary teachers. It was discussed the themes that emerged from a set of discussions and activities developed over three months with a group of 13 women primary teachers, in the city of São José dos Campos, São Paulo. The authors of this work come from researches in creative musical processes (BARRET, 2012; DELIÈGE AND WIGGINS, 2006), in humanizing music education (JOLY & SEVERINO, 2016), community music (HIGGINS, 2012) and musical lifelong learning (BJØRKVOLD, 2018). Inspired by participatory action research (FALS-BORDA, 1987), this study elaborated, applied, recorded and analysed activities of creation and improvisation with a group of teachers, seeking to understand from experience and reflection with this community, the role of the creative process in expanding the learning possibilities of the adult beginner. The results revealed the specificities of adult musical learning and that creative processes can have multiple functions in the development of musicality: helping in the process of awareness and organization of participants' musical knowledge, assisting to reveal the dialogue between subject and culture, promoting emancipated behaviours and aiding in overcoming the mimetic process.